Unmasked eaudiobook The final years of michael jackson. - Halperin, Ian (Tantor Media, 2009)
In late December 2008, New York Times bestselling author Ian Halperin told the world that Michael Jackson had only six months to live. His investigations into Jackson's failing health made headlines around the globe. Six months later, the King of Pop was dead. Whatever the final autopsy results reveal, it was greed that killed Michael Jackson. Friends and associates paint a tragic picture of the last years and days of his life as Jackson made desperate attempts to prepare for the planned concert series at London's O2 Arena in July 2009. These shows would have earned millions for the singer and his entourage, but he could never have completed them, not mentally and not physically. Michael knew it and his advisers knew it. Anyone who caught even a fleeting glimpse of the frail old man hiding beneath the costumes and cosmetics would have understood that the London tour was madness. Why did it happen this way? After an intense five-year investigation, Halperin uncovers the real story of Michael Jackson's final years, a suspenseful and surprising thriller.